The consistency between professed teaching practices and assessment practices: A case in mathematics class - Yoppy Wahyu Purnomo; Amrita Kaur; Siti Noor Binti Ismail; Didi Suryadi; Sutawanir Darwis (Beta: Jurnal Tadris Matematika, 2018)
[English]: The purpose of this research was to (1) develop scales for measuring teaching practices and assessment practices in mathematics class; (2) identify the profile of teaching practices and assessment practices in mathematics class; and (3) examine the consistency between relevant factors in teaching practices and assessment practices in mathematics class. The methods of cross-sectional surveys and a scale development study were used to achieve that purpose. The participants in this research included two sample groups of primary school teachers in Jakarta. The first sample consisted of 252 teachers and the second sample consisted of 325 teachers. This research found that there were two factors in each dimension of teachers’ practices in mathematics class. Teaching practices included the relational and instrumental practices, while the assessment practices included the assessment for learning and assessment of learning. This research also found that most of the teachers leaned toward traditional practices for both teaching practices and assessment practices, and that there was a consistency between relevant factors in those teaching and assessment practices. A more detailed discussion can be found in the findings and discussion section. Keywords: Assessment practices, Teaching practices, Mathematics class, Scale development study, Cross-sectional Survey [Bahasa]: Penelitian ini bertujuan untuk (1) mengembangkan sebuah skala untuk mengukur praktik mengajar dan penilaian di kelas matematika; (2) mengidentifikasi profil praktik mengajar dan praktik penilaian di kelas matematika; dan (3) mengkaji konsistensi antar faktor-faktor yang bersesuaian pada praktik mengajar dan penilaian di kelas matematika. Metode survei cross-sectional dan studi pengembangan skala digunakan untuk menggapai tujuan tersebut. Partisipan dalam penelitian ini mencakup dua kelompok sampel guru sekolah dasar di Jakarta. Sampel pertama adalah 252 guru dan sampel kedua adalah 325 guru. Temuan penelitian ini mendapati terdapat dua faktor di setiap dimensi praktik guru di kelas matematika. Praktik mengajar mencakup faktor praktik relasional dan instrumental, sedangkan praktik penilaian mencakup faktor praktik assessment for learningdan assessment of learning. Penelitian ini juga menemukan bahwa sebagian besar guru mengarah pada praktik-praktik tradisional baik praktik mengajar maupun praktik penilaian, dan terdapat konsistensi antar faktor yang bersesuaian pada praktik mengajar dan penilaian tersebut. Diskusi lebih detail dapat ditemukan pada bagian hasil dan pembahasan. Kata kunci: Praktik penilaian, Praktik mengajar, Kelas Matematik, Studi Pengembangan Skala, Survei cross-sectional